Sovereign vs. corporate debt and default: More similar than you think - Gita Gopinath; Josefin Meyer; Carmen M. Reinhart; Christoph Trebesch (Kiel Institute for the World Economy (IfW Kiel), 2025)
Theory suggests that corporate and sovereign bonds are fundamentally different, also because sovereign debt has no bankruptcy mechanism and is hard to enforce. We show empirically that the two assets are more similar than you think, at least when it comes to high-yield bonds over the past 20 years. We use rich new data to compare high-yield US corporate ("junk") bonds to high-yield emerging market sovereign bonds 2002-2021. Investor experiences in these two asset classes were surprisingly aligned, with (i) similar average excess returns, (ii) similar average risk-return patterns (Sharpe ratios), (iii) similar default frequency, and (iv) comparable haircuts. A notable difference is that the average default duration is higher for sovereigns. Moreover, the two markets co-move differently with domestic and global factors. US "junk" bond yields are more closely linked to US market conditions such as US stock returns, US stock price volatility (VIX), or US monetary policy.
Keywords: F3; G1; F4; 330; Sovereign debt and default; default risk; corporate bonds; corporate default; junk